Current and emerging therapeutic options for the management of functional dyspepsia. (11th February 2020) - Vandenberghe, A.; Schol, J.; Van den Houte, K.; Masuy, I.; Carbone, F.; Tack, J.
ABSTRACT: Introduction : Functional Dyspepsia (FD), defined as chronic symptoms originating from the gastroduodenal region in absence of readily identifiable organic disease, is one of the most common gastrointestinal disorders. FD is divided into two subgroups: Post-Prandial Distress Syndrome (PDS) or meal-related FD, characterized by postprandial fullness and early satiation, and Epigastric Pain Syndrome (EPS) or meal-unrelated FD, characterized by epigastric pain and burning. Areas covered : This review summarizes the existing and off-label therapeutic options for FD. Expert opinion : The identification of mechanisms, the Rome IV classification, the reduction of PDS/EPS overlap and pictograms for symptom identification allow a better diagnosis and a more targeted treatment choice. Acotiamide, a first-in-class prokinetic agent available only in Japan and India, is the only agent of proven efficacy for FD, but clinicians use acid-suppressive therapy, prokinetics, neuromodulators and herbal therapies for treating FD symptoms. New emerging targets are duodenal low-grade inflammation with eosinophils and duodenal or other modified luminal microbiota.